THE INFLUENCE OF CONVENIENCE, TRUST, SECURITY AND BENEFITS OF SHOPEE ONLINE SHOPPING IN THE PESANTREN ENVIRONMENT - Amatudzil Izzah; Yuniorita Indah Handayani; Bagus Qomaruzzaman (MBA : Journal of Management and Business Aplication, 2024)
This research is entitled "(Effect of convenience, Trust, Security in Transaction and Shopping advantages on online purchase decision at shopee in an anvironment of students pp Nurur Rahmah)". This study aims to determine directly and indirectly the influence of ease of access to applications, prices, consumer confidence, benefits for buyers and sellers and transaction security on online purchasing decisions in Islamic boarding schools. The population of this study were students who had used the Shopee application for shopping. The sample used was 50 respondents. Sampling technique with Non-Probability Sampling (Accidental Sampling). The data analysis method uses path analysis with the help of SPSS 25. The tests used are instrument data tests (validity test, reliability test), classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), sobel test, coefficient of determination, t test and F test. The results showed that there was no direct effect of the convenience variable and buyer's trust on customer satisfaction.